Sodium butyrate treatment and fecal microbiota transplantation provide relief from ulcerative colitis-induced prostate enlargement - Dong, Weimin; Zheng, Jiefang; Huang, Yiqiao; Tan, Huijing; Yang, Shengbang; Zhang, Zhiming; Liang, Xue; Liu, Hao; Zeng, Guohao; Xu, Haoming; Jiang, Xianhan; Zhong, Weide (Frontiers in Cellular and Infection Microbiology, 2022)
The ability to regulate the gut environment has resulted in remarkable great breakthroughs in the treatment of several diseases. Several studies have found that the regulation of the gut environment might provide relief from the symptoms of benign prostatic hyperplasia. However, the correlation between the gut microenvironment and the colon and prostate glands is still unknown. We found that ulcerative colitis (UC) induced an increase in prostate volumes that could be reversed by sodium butyrate (NaB) and fecal microbiota transplantation (FMT). The mechanism by which UC induced changes in the prostate gland was examined via RNA-Seq. The results show that the expression level of GPER was significantly lower in the prostate gland of UC mices than in normal mices. The expression of GPER could be increased via treatment with NaB or FMT. We found that prostate tissues exhibited higher butryic acid levels after they were treated with NaB or FMT. In experiments conducted in vitro, NaB or the fecal filtrate (FF) from healthy mice up-regulated of the expression of GPER, inhibited cell growth, and induced apoptosis in BPH-1 cells. These changes could be alleviated by treatment with the G15 or in GPER-silenced cells.